Impact of Climate Policy Uncertainty on Regional New Quality Productive Forces in China - Haoyang Lu; Alistair Hunt (Urban Science)
In the context of China’s strategic push toward high-quality development, the concept of new quality productive forces (NQPF)—which emphasizes technological innovation, green transformation, and digital upgrading—has received a lot of attention. However, the increasing volatility and ambiguity in climate-related policymaking present a serious institutional challenge. This study addresses the underexplored question of how climate policy uncertainty (CPU) affects the regional development of NQPF in China. Unlike traditional productivity, NQPF relies on long-term innovation and sustainable investment, which are highly sensitive to external policy signals. Drawing on panel data from 30 Chinese provinces between 2013 and 2021, this paper uses fixed-effects regressions to empirically assess the influence of CPU on NQPF. The findings reveal that CPU significantly suppresses the development of NQPF, but this effect is mitigated by financial inclusion, carbon market participation, and strong local government sustainability performance. This paper provides new insight into the risks posed by climate uncertainty to economic development and highlights institutional tools that can buffer its negative effects.